Implementing the edge enhancement with vortex filter in both linear and nonlinear optics - Xu, Diefei; Zhang, Wuhong (Frontiers in Physics, 2023)
The edge enhancement technique, as an effective method to represent the boundary of objects, plays an important role in image processing. Among them, the vortex filtering, which is based on the radial Hilbert transformation, has been paid great attention due to its ability to achieve isotropic and anisotropic edge enhancement. Recent years have witnessed a growing interest in the nonlinear vortex filter to skillfully realize the visualization of the object edge under invisible light irradiation. In this paper, we start from reviewing the achievements have been made with the vortex filtering technique in linear optics, and then discussed the recent processes of the scalar and vector vortex filter in nonlinear optics. We hope that the nonlinear optical vortex filter can motivate some promising applications in biological edge imaging with visible light-sensitive specimens.